Effects of the standardized ileal digestible valine : lysine ratio on performance, milk composition and plasma indices of lactating sows. (5th December 2016) - Xu, Yetong; Zeng, Zhikai; Xu, Xiao; Tian, Qiyu; Ma, Xiaokang; Long, Shenfei; Piao, Meijing; Cheng, Zhibin; Piao, Xiangshu
Abstract: To determine the effects of standardized ileal digestible (SID) valine : lysine ratio on the performance, milk composition and plasma indices of lactating sows, 32 Large White × Landrace sows (219.78 ± 7.15 kg body weight; parity 1.82 ± 0.62) were allotted to one of four dietary treatments with eight sows per treatment based on parity, back fat thickness and body weight. The sows were fed corn‐soybean meal‐based diets containing 63, 83, 103 or 123% SID valine : lysine from day 107 of gestation until day 28 of lactation. The average daily feed intake of sows and daily weight gain of piglets increased linearly ( P  < 0.05) while back fat loss decreased linearly ( P  < 0.05) as the SID valine : lysine ratio increased. All of the analyzed amino acids in sow colostrum and valine concentrations of sow and piglet plasma increased linearly ( P  < 0.05) with the increasing SID valine : lysine ratio. In conclusion, 88 and 113% dietary SID valine : lysine ratios were optimal to achieve minimum back fat loss and maximum piglet growth rate using a linear‐break point model which exceeds the requirement of 85% that is estimated by the National Research Council (2012).